1932
DOI: 10.1113/jphysiol.1932.sp002899
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the components of lecithine upon deposition of fat in the liver

Abstract: THE results of the experiments in which purified lecithine from two sources, egg yolk and fresh beef liver, has been shown to prevent deposition of fat in the livers of normal rats [Best, Hershey and Huntsman, 1932] have led us to study the effects of feeding various components of lecithine. It appeared possible that the oleic or other unsaturated fatty acid, the glycerophosphate, the choline, some combination of two or more of these factors, or the whole lecithine molecule, might be the active agent. The gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
2

Year Published

1934
1934
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(46 citation statements)
references
References 1 publication
2
42
0
2
Order By: Relevance
“…Very early studies since the 1930s have shown that high-fat diet-induced hepatic steatosis in both healthy and diabetic animals could be prevented by ingestion of betaine or choline [22,23]. In the rat [24], hamster [25], dog [19] and monkey [26], choline deficiency results in liver dysfunction owing to accumulation of TG [27][28][29][30] and DAGs [31] within the hepatocyte.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Very early studies since the 1930s have shown that high-fat diet-induced hepatic steatosis in both healthy and diabetic animals could be prevented by ingestion of betaine or choline [22,23]. In the rat [24], hamster [25], dog [19] and monkey [26], choline deficiency results in liver dysfunction owing to accumulation of TG [27][28][29][30] and DAGs [31] within the hepatocyte.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The nutritional importance of choline was described 70 years ago in a classic study (1). A major phenotype of choline deficiency was the accumulation of lipid in the liver.…”
mentioning
confidence: 99%
“…2). This apparent defect in lipoprotein secretion would be expected to account for at least some of the accumulating hepatic triacylglycerol (TG) 1 in choline-deficient animals and was proposed to be due to impaired phosphatidylcholine (PC) biosynthesis via the CDP-choline pathway. Advances in hepatocyte culture and lipoprotein isolation permitted a more rigorous evaluation of the role of PC biosynthesis in lipoprotein secretion in the 1980s.…”
mentioning
confidence: 99%
“…Studies investigating the importance of the CDP-choline pathway in lipoprotein metabolism have primarily consisted of feeding choline-deficient (CD) diets to animals (15)(16)(17), or applying CD medium to hepatocytes or other cells in culture (18 -20). It has been well established that hepatic and plasma PC concentrations are reduced in rats fed a CD diet.…”
mentioning
confidence: 99%